Effect of particle size on additive manufacturing of complex architecture of silicon carbide - Jana A.; Das M.; Tiwari S.; Basha S.S.; Gautam A.R.S.; Panda S.K.; Mitra R.; Kumar S.; Devasia R.; Tiwary C.S. (My University, 2025)
The high-temperature stability, chemical inertness, and enhanced mechanical strength of SiC are utilized for the fabrication of space components. Here, environment-friendly water-based SiC ceramic inks were developed using different size SiC powders. The relation between the SiC particle size and rheological properties is established. The additive manufacturing conditions for SiC are optimized which shows the compressive strength of ∼1.21 MPa. This strength was obtained in the green state for SiC having an average particle size of ∼0.5 μm. As the milling time increases, particle size decreases which make better dispersion in the ink system and it shows good shear-thinning characteristics. The optimum sintering temperature (1400 °C) results in improved compressive strength of ∼80 MPa with a relative density of ∼81%. The current printing method can produce complex ceramic components which can be utilized for manufacturing complex aerospace components. © 2023 Elsevier Ltd and Techna Group S.r.l.